Polygamy among Muallaf in Manado: Islamic Legal Perspectives and Social Challenges - Sarib, Suprijati; Yusnita, Eti; Utama, Cholidah; Zain, Muhammad Irfanul Hakim (JURIS (Jurnal Ilmiah Syariah), 2024)
The practice of polygamy is often a controversial topic and raises questions about religious and cultural identity. Although Islamic law permits polygamy under certain conditions, how this is understood and applied by the convert community in a Christian setting is complex. This study explores the dynamics of polygamy among converts (Muallaf) in the multicultural environment of Manado, Indonesia, from the perspective of Islam and society. Using an empirical normative approach, the study involved 35 informants, consisting of 25 Muallaf who were married in Islam and ten who were engaged in polygamous marriages. Data was collected through in-depth interviews, and the analysis identified common patterns and significant findings, focusing on factors influencing attitudes towards polygamy. The results revealed differences in views among Muallaf regarding polygamy; some accept this practice as part of Islamic teachings, while others reject it as contrary to their previous values. Factors such as religious interpretation, pre-conversion values, and legal and social barriers affected their attitudes toward polygamy. The problematic legal hurdles of obtaining polygamy permits in court highlight additional challenges in implementing this practice in Manado. Nevertheless, polygamy remains a controversial issue in this predominantly Christian society, reflecting the complexity of the interaction between religion and culture. This research provides important insights into how polygamy is perceived and practiced in multicultural environments and the challenges Muallaf faces in understanding and applying Islamic law in their social contexts.